Existence of Time Periodic Solutions to Boundary Value Problem of One-dimensional Semilinear Viscoelastic Dynamic Equation with Memory (Journal of Partial Differential Equations, 1997)
In this paper, we prove the existence of time-periodic solutions to the boundary value problem of semilinear one-dimensional dynamical equation for viscodastic materials.